Ways to Develop the Creative Qualities of Technological Education Teacher - Chorshanbiyevich, Dusyarov Xudoymurod (Indonesian Journal of Innovation Studies, 2022)
This article analyzes ways to develop the creative qualities of technological education teacher and emphazises the development of world civilization. Therefore, there are the concepts of "innovation" and "innovation", and it is necessary to point out the main differences between them. At the same time, new directions of activity will be opened in this article.